A universal panel of STR loci for the study of polymorphism of the species Canis lupus and forensic identification of dog and wolf - A. E. Hrebianchuk; I. S. Tsybovsky (Вавиловский журнал генетики и селекции, 2024)
Commercial panels of microsatellite (STR) loci are intended for DNA analysis of the domestic dog (Canis lupus familiaris) and, therefore, when genotyping the Grey wolf (Canis lupus lupus), most markers reveal significant deviations from the Hardy–Weinberg equilibrium and have a low informative value, which complicates their use in a forensic examination. The aim of this study was to select STR markers that equally effectively reflect population polymorphism in the wolf and the dog, and to create a universal panel for the identification of individuals in forensic science. Based on the study of polymorphisms of 34 STR loci, a CPlex panel of 15 autosomal loci and two sex loci was developed, which is equally suitable for identifying wolfs and dogs. Analysis of molecular variance (AMOVA) between samples revealed significant differentiation values (FST = 0.0828, p < 0.05), which allows the panel to be used for differentiating between wolf and dog samples. For the first time in the forensic examination of objects of animal origin in the Republic of Belarus, population subdivision coefficients (θ-values) were calculated for each of the 15 STR loci of the test system being reported. It was shown that the values of the genotype frequency, when averaged over all studied animals without and with considering the θ-value, differ by three orders of magnitude (3.39 · 10–17 and 4.71 · 10–14, respectively). The use of population subdivision coefficients will provide the researcher with the most relevant results of an expert identification study. The test system was validated in accordance with the protocol of the Scientific Working Group on DNA Analysis Methods. A computational tool was developed to automate the analysis of genetic data on the wolf and dog in the forensic examination; two guides were approved for practicing forensic experts. This methodology is being successfully used in expert practice in investigating cases of illegal hunting, animal abuse and other offenses in the Republic of Belarus.